The validity of the EMG and MMG techniques to examine muscle hypertrophy. (28th February 2019) - Hill, Ethan C; Housh, Terry J; Keller, Joshua L; Smith, Cory M; Schmidt, Richard J; Johnson, Glen O
Abstract: Objective : The purpose of this investigation was to examine the ability of the electromyographic (EMG) and mechanomyographic (MMG) amplitude versus torque relationships to track group and individual changes in muscle hypertrophy as a result of resistance training. Approach : Twelve women performed four weeks of forearm flexion blood flow restriction (BFR) resistance training at a frequency of three times per week. The training was performed at an isokinetic velocity of 120° · s −1 with a training load that corresponded to 30% of concentric peak torque. Muscle hypertrophy was determined using ultrasound-based assessments of muscle cross-sectional area from the biceps brachii. Training-induced changes in the slope coefficients of the EMG amplitude and MMG amplitude versus torque relationships were determined from the biceps brachii during incremental (10%–100% of maximum) isometric muscle actions. Main results : There was a significant ( p    <  0.001; d   =  2.15) mean training-induced increase in muscle cross-sectional area from 0 week (mean  ±  SD  =  5.86  ±  0.65 cm 2 ) to 4 weeks (7.42  ±  0.80 cm 2 ), a significant ( p    =  0.023; d   =  0.36) decrease in the EMG amplitude versus torque relationship (50.70  ±  20.41 to 43.82  ±  17.76 µ V · Nm −1 ), but no significant ( p    =  0.192; d   =  0.17) change in the MMG amplitude versus torque relationship (0.018  ±  0.009 to 0.020  ±  0.009 m · s −2 · Nm −1 ). There was, however, great variability for the individual responses for the EMG and MMG amplitude versus torque relationships. Significance : The results of the present study indicated that the EMG amplitude, but not the MMG amplitude versus torque relationship was sensitive to mean changes in muscle cross-sectional area during the early-phase of resistance training. There was, however, great variability for the individual EMG amplitude versus torque relationships that limits its application for identifying individual changes in muscle hypertrophy as a result of BFR.